2016
DOI: 10.1016/j.aap.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Crash risk analysis for Shanghai urban expressways: A Bayesian semi-parametric modeling approach

Abstract: Urban expressway systems have been developed rapidly in recent years in China; it has become one key part of the city roadway networks as carrying large traffic volume and providing high traveling speed. Along with the increase of traffic volume, traffic safety has become a major issue for Chinese urban expressways due to the frequent crash occurrence and the non-recurrent congestions caused by them. For the purpose of unveiling crash occurrence mechanisms and further developing Active Traffic Management (ATM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 22 publications
(19 reference statements)
6
24
1
Order By: Relevance
“…Therefore, the significant variables in four time-slice models were investigated. Average speed was found to have significant negative effect on the odds of crash occurrence, which is consistent with previous studies , Ahmed et al 2012a, b, Ahmed and Abdel-Aty 2012, Xu et al 2012, Shi and Abdel-Aty 2015, Yu et al 2016, Yuan et al 2018. The left turn volume was surprisingly found to be negatively correlated with the odds of crash occurrence, which might be explained as the higher left turn volume may increase the driver awareness when approaching the entering approach, which may improve the safety performance.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the significant variables in four time-slice models were investigated. Average speed was found to have significant negative effect on the odds of crash occurrence, which is consistent with previous studies , Ahmed et al 2012a, b, Ahmed and Abdel-Aty 2012, Xu et al 2012, Shi and Abdel-Aty 2015, Yu et al 2016, Yuan et al 2018. The left turn volume was surprisingly found to be negatively correlated with the odds of crash occurrence, which might be explained as the higher left turn volume may increase the driver awareness when approaching the entering approach, which may improve the safety performance.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the slice 2 model indicate that the average speed, upstream left-turn volume, downstream green ratio, and rainy indicator are significantly associated with the crash risk on urban arterials. In general, these finding are consistent with previous studies, in which the average speed was found to have significant negative impact on crash occurrence Ahmed et al, 2012a, b;Ahmed and Abdel-Aty, 2012;Shi and Abdel-Aty, 2015;Xu et al, 2012;Yu et al, 2016), while adverse weather (Ahmed et al, 2012a;Xu et al, 2013a) were found to be positively correlated with crash likelihood. In terms of the effect of traffic volume, only the upstream left-turn volume was found to have significant effect on crash likelihood, which indicates that more vehicles from the intersecting road segment left turning into the subject segment may increase the crash risk on the segment.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Finally, the slice 2 model was selected to conduct further interpretation and model comparison. Based on the estimation results in the slice 2 model, four variables were found to be significantly associated with the crash occurrence on urban arterials: (1) the negative coefficient (-0.025) of average speed indicates that higher average speed tends to decrease the crash risk, which is consistent with other studies Ahmed et al, 2012a, b;Ahmed and Abdel-Aty, 2012;Shi and Abdel-Aty, 2015;Xu et al, 2012;Yu et al, 2016). This could be explained as the traffic condition with higher average speed, which represents more smooth traffic flow, could have better safety performance.…”
Section: Modeling Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…e crash risk analysis models were developed for total crashes and timerelated crashes to reveal the significant factors that affect crash risk [17]. In addition, typical scenarios leading to an accident were found from the modelling results.…”
Section: Introductionmentioning
confidence: 99%